Quantitative Evaluation of Blood Perfusion to Nerves Included in the Anterolateral Thigh Flap using Indocyanine Green Fluorescence Angiography: A Different Contrast Pattern between the Vastus Lateralis Motor Nerve and Femoral Cutaneous Nerve - Tanaka, Kentaro; Okazaki, Mutsumi; Yano, Tomoyuki; Miyashita, Hiroki; Homma, Tsutomu; Tomita, Makoto (Journal of Reconstructive Microsurgery, 2015)
Background Better postoperative results can be expected in nerve reconstruction when vascularized nerve grafts are used. Previous studies reported reconstruction with flaps including “vascularized” nerves; however, few have evaluated blood supply to these nerves. The aim of this study was to quantitatively assess blood perfusion to nerves included in anterolateral thigh (ALT) flaps by indocyanine green (ICG) fluorescence angiography.Patients and Methods Participants comprised eight patients who underwent reconstructive surgery with nerve defects using free ALT flaps, including the vastus lateralis motor nerve and/or femoral cutaneous nerve. Intraoperative ICG fluorescent angiography was performed. Time after the drug injection and the intensity of fluorescence in these nerves were analyzed as time–intensity curves. Maximum intensity (Imax), time to Imax (Tmax), and time at the beginning of intensity elevation (Te) were measured at three points: Point C, the central portion of the flap-attached region of the nerve; Point P, 2 cm from the proximal flap-attached edge; and Point D, 2 cm from the distal edge.Results Imax and Te at point C and Imax/Tmax-Te at point P were significantly different between these two nerves (p = 0.03125, p = 0.02895, p = 0.03125, respectively). Fluorescence in the vastus lateralis motor nerve was slightly quicker and stronger than that in the femoral cutaneous nerve, and also exhibited an axial pattern of fluorescence.Conclusion Intraoperative ICG fluorescent angiography can be used to determine which nerve is better for nerve reconstruction. The indexes of Imax, Te, and Imax/Tmax-Te may be the suitable criteria for decision making regarding donor nerve selection.
Keywords: vascularized nerve graft; vastus lateralis motor nerve; femoral cutaneous nerve; anterolateral thigh flap; indocyanine green fluorescent angiography